2009
DOI: 10.1016/j.fertnstert.2008.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of multiple leiomyomata uteri and matched normal tissue from a single patient

Abstract: Objective-To identify differentially expressed genes between fibroid and adjacent normal myometrium in an identical hormonal and genetic background.Design-Array analysis of 3 leiomyomata and matched adjacent normal myometrium in a single patient. Setting-University of Colorado Hospital.Patient(s)-A single female undergoing medically indicated hysterectomy for symptomatic fibroids.Interventions(s)-mRNA isolation and microarray analysis, reverse-transcriptase polymerase chain reaction, western blotting and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 69 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…In addition, cellular proliferation stimulated by growth factors and/or steroid hormones is one of the mechanisms associated with the increased tumour volume observed in ULs [42], [43]. The COL3A1 , IGFBP5 and FGFR1 genes are directly associated with the typical features found in ULs (including fibroid formation), which strongly suggests their involvement in ULs pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cellular proliferation stimulated by growth factors and/or steroid hormones is one of the mechanisms associated with the increased tumour volume observed in ULs [42], [43]. The COL3A1 , IGFBP5 and FGFR1 genes are directly associated with the typical features found in ULs (including fibroid formation), which strongly suggests their involvement in ULs pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…What distinguishes the leiomyomata from its surrounding myometrium is the excessive and disorganized ECM that surrounds the cells. The excessive ECM secreted by the leiomyoma cells in vivo is supported by the altered expression of the genes specific to these ECM proteins, as compared with the myometrium (1,(22)(23)(24)(25)(26). We have demonstrated that the immortalized myometrium and leiomyoma cells, when grown in 3D collagen-1 culture, retain the in vivo characteristics of the tissues they are derived from as well as the characteristic spindle shape of the SMC.…”
Section: Discussionmentioning
confidence: 83%
“…Although a large number of genes are differentially expressed in fibroids compared with myometrium (Tsibris et al 2002, Skubitz & Skubitz 2003, Arslan et al 2005, Luo et al 2005a, 2005b, Zaitseva et al 2006, Dimitrova et al 2009, it is likely that most of these changes occur as a consequence of the fibroids' presence and do not cause fibroid development. We have targeted NR2F2 and CTNNB1 in this study based on their significant potential for a causal role in uterine fibroid pathophysiology , Tanwar et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, uterine fibroids are the single-most common reason for hysterectomy in developed countries (Treloar et al 1999, Farquhar & Steiner 2002, Garry 2005, and despite their large healthcare burden, there is limited understanding of the molecular mechanisms that drive fibroid pathophysiology. Gene profiling studies by our laboratory and others have identified a large number of genes with altered expression in fibroid tumours compared with myometrium (Tsibris et al 2002, Skubitz & Skubitz 2003, Arslan et al 2005, Luo et al 2005a, 2005b, Zaitseva et al 2006, Dimitrova et al 2009). However, it is hypothesised that the majority of these genes are differentially expressed as a consequence of the changed microenvironment caused by the fibroids' presence and are not causal to fibroid development.…”
Section: Introductionmentioning
confidence: 98%